Single-Cell RNA Sequencing of Arabidopsis Leaf Tissues Identifies Multiple Specialized Cell Types: Idioblast Myrosin Cells and Potential Glucosinolate-Producing Cells - Maeda, Taro; Sugano, Shigeo S; Shirakawa, Makoto; Sagara, Mayu; Ito, Toshiro; Kondo, Satoshi; Nagano, Atsushi J (Plant and cell physiology, 2023)
The glucosinolate–myrosinase defense system (GMDS), characteristic of Brassicales, is involved in plant defense. Previous single-cell transcriptomic analyses have reported the expression profiles of multiple GMDS-related cell types (i.e. myrosinase-rich myrosin idioblasts and multiple types of potential glucosinolate synthetic cells as well as a candidate S-cell for glucosinolate accumulation). However, differences in plant stages and cell-type annotation methods have hindered comparisons among studies. Here, we used the single-cell transcriptome profiles of extended Arabidopsis leaves and verified the distribution of previously used markers to refine the expression profiles of GMDS-associated cell types. Moreover, we performed beta-glucuronidase promoter assays to confirm the histological expression patterns of newly obtained markers for GMDS-associated candidates. As a result, we found a set of new specific reporters for myrosin cells and potential glucosinolate-producing cells.